PERBANDINGAN MODEL REGRESI WEIBULL DAN REGRESI COX PROPOSIONAL HAZARD - Mayawi Mayawi; Nurhayati Nurhayati; Novita Serly Laamena; Ariestha Widyastuty Bustan; Munazat Salmin; Taufan Talib (Science Map Journal, 2022)
This study aims to determine the model of Acute Myocardial Infarction using the Weibull Regression and Cox Proportional Hazard Regression methods to determine the factors that significantly influence the length of time for recovery of acute myocardial infarction patients. The results of this study indicate that the factors that significantly influence the recovery time of acute myocardial infarction patients are age, onset, number of secondary diagnoses and duration of pain. Based on the AIC value, the Weibull regression model is the best regression model because the AIC value is smaller, namely 292.883 compared to the Cox Proportional Hazard regression model with an AIC value of 493.3971